Some peculiarities of organising the interrogation of a juvenile (minor) victim under martial law - M. V. Kryvonos (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of the Code of Criminal Procedure and the scientific work of scholars and practitioners, it has been established that criminal justice for juveniles (minors) should be structurally separated from adult justice, carried out in different forms, and should include their social and psychological support and rehabilitation. Such a system should recognise that children are not adults, they are largely dependent on adults and society, have a lower level of emotional, mental and intellectual maturity, and therefore require special treatment appropriate to their age and level of development. In this regard, the article identifies the main tactical approaches to the most optimal organisation of interrogation of a juvenile (minor) victim under martial law. Proposals have been made regarding the choice of place (special “friendly” premises or rooms and alternative places) and time of such investigative (detective) action, as well as the investigator (detective) or prosecutor who will conduct the interrogation. Options for providing professional assistance by a teacher, psychologist and doctor, who must be present during the interrogation of a minor or underage victim, are also suggested. The investigator (inquirer) and prosecutor are provided with practical recommendations on organising and conducting interrogation of a juvenile (minor) victim, using modern interrogation methods, and the procedure for conducting it, which will increase the efficiency of the procedural action and ensure compliance with the basic principles of child-friendly justice.